Surgical and medical management of 05 cases of acute intestinal obstruction on pregnancy in university hospital center of Treichville, Côte d’Ivoire - Traore, Lassina; Ango, Privat D.; Anoh, N’djeche; Kouadio, Laurent; Dia, Lamine J. M. H.; Kouadio, Germain K. (International Surgery Journal, 2018)
From January 2003 to December 2017, the authors report five cases of acute intestinal obstruction during pregnancy. Two of them were received in digestive and proctological surgery emergencies. The other three patients were received urgently from the obstetrics and gynecology department. This association is a rare event. Clinical polymorphism delays the therapeutic management. In 1/5 cases only the diagnosis of occlusion on pregnancy was made. In 2/5 of the cases the diagnosis of occlusion was made and that of the pregnancy which at the 1st trimester was unknown. In last 2/5 of cases the pregnancies were at the 3rd trimester, the diagnosis of occlusion during pregnancy was made intraoperatively; Caesarean section being indicated for the fetal in distress on probable urinary tract infection. Authors did not have any maternal-fetal deaths. Through five cases of this association and a review of the literature, authors highlight the diagnostic and therapeutic difficulties and the therapeutic attitudes likely to improve the feto-maternal prognosis. This fetal prognosis depends essentially on the age of the pregnancy and the speed of the management.